Analysis of Students' Mathematical Literacy Ability in Solving Ethnomathematical Problems on SPLDV Material Judging from Student Learning Interests - Sulistiawati, Yuni; Swastika, Annisa; Nurcahyo, Adi (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2024)
Interest in learning as a driving factor has an important role in improving students' mathematical literacy skills. One effort to attract students' attention is to make learning innovations such as incorporating ethnomathematics in learning. This study aims to describe students' mathematical literacy ability in solving ethnomathematical problems on spldv material in terms of student learning interests. This research is a qualitative research with a descriptive approach. The subjects of this study were 3 out of 29 grade VIIIB students who had been selected for high, medium and low learning interest categories. Data collection was carried out by questionnaires, tests and interviews. The main instrument in this study is an ethnomathematics-based mathematical literacy test. Data analysis techniques use interactive analysis. The results showed that the cause of students' low mathematical literacy ability was due to low interest in learning. Students with a high interest in learning are able to meet all indicators of mathematical literacy. Students with an interest in learning are having difficulty at number 1, but at question number 2 are able to meet all indicators of mathematical literacy. While students with low interest in learning for questions number 1 only meet indicators 1), 2), 3), 6) and at number 2 only meet indicators 1), 2), and 3) only. That is, students with high and moderate interest in learning have mathematical literacy skills that work well, while students with low interest in learning need teacher help to improve their mathematical literacy skills.